EKOSISTEM INKUBASI BISNIS BERBASIS PESANTREN - Zainur Ridho; Muhammad Jamaluddin; Abdul Ghafur (ESA : JURNAL KAJIAN EKONOMI SYARIAH, 2026)
This study aims to analyze the Islamic boarding school ecosystem as a center for business incubation based on Islamic values, using a case study of the Al-Mashduqiah Islamic Boarding School in Patokan, Kraksaan, Probolinggo. As an Islamic educational institution undergoing transformation, Islamic boarding schools now function not only as centers of education and da'wah, but also as drivers of the community's economy through the development of cooperatives and student business units. This study uses a descriptive qualitative approach with in-depth interviews, participatory observation, and documentation of pesantren caregivers, cooperative administrators, santri, and the surrounding community. The results show that the Al-Mashduqiah Islamic Boarding School Cooperative (Kopontren) plays a strategic role in creating an independent and sustainable business ecosystem for Islamic boarding schools. Through cooperative units, boarding school wholesalers, and santripreneur training activities, Islamic boarding schools are able to combine spiritual, social, and economic values into a single practice-based learning system. Kopontren Al-Mashduqiah functions effectively as a sharia business incubation center, which not only meets the economic needs of the pesantren, but also fosters the entrepreneurial spirit of santri and strengthens the economic independence of the community. It also serves as a pesantren business incubation ecosystem that not only supports the internal economic needs of the pesantren, but also becomes a medium for learning, character building, and real Islamic economic da'wah. Keywords: ecosystem, business incubation, pesantren.